Ingestão de betaglucanas de levedura no controle da massa corpórea de roedores obesos e não obesos: uma revisão sistemática de estudos pré-clínicos - Canaan, Marcelo Martins (2021)
Obesity is a chronic non-communicable disease (NCDs) of multifactorial etiology, with high morbidity and mortality and that generates significant costs for the health system. Dietary fiber supplementation has been studied as a promising strategy in the treatment of obesity and its comorbidities. Among the fibers, beta-glucans (BG) stand out, polysaccharides widely distributed in the cell wall of cereals, grasses, as well as fungi and some bacteria. BG from microorganisms have established and relevant activity on the immune system. However, its effectiveness on metabolic parameters is still poorly studied or controversial. In this sense, the present systematic review and meta-analysis was carried out to answer the question: Can the consumption of yeast BG favor the loss of body mass in obese and non-obese animals? To answer this question, the PICO strategy (PICO question) was used, in which: obese and non-obese rodents (Population) were evaluated, submitted to oral administration of yeast BG (Intervention) compared to animals receiving placebo (Comparison) in relation to changes in body mass (Outcome). Two independent reviewers searched six databases (PubMed, Scopus, Web of Science, Embase, Science Direct, Scielo) and Opengrey platform until July 2021. This report followed the PRISMA 2020 guidelines (Preferred Reporting Items for Systematic Reviews and Meta-Analysis) and it was registred at PROSPERO (CRD42021267788). The risk of bias was determined using the SYRCLE protocol (Risk of bias tool for animal studies) and the methodological quality was assessed according to the ARRIVE (Animal Research Reporting In Vivo Experiment) criteria. The search in the databases returned 2467 articles. Of these, 30 articles were selected for full text evaluation and seven articles (one of which evaluated both obese and non-obese animals) remained based on eligibility criteria. The effects of BG intake on body weight were analyzed based on two groups: 1) obese animals (n=4 studies); and 2) non-obese animals (n=4 studies). Even though most studies on obese rodents (75%) indicated a reduction in body weight (qualitative analysis), the meta-analysis showed this was not significant (mean difference -1.35g - 95% CI -5.14:2.45). No significant effects were also observed for non-obese animals. Overall, the risk of bias was low, but most studies failed to provide clear information about randomization and blinding. ARRIVE scores showed 70% of the domains classified as excellent and 30% as average. It was concluded that the ingestion of yeast BG barely affect body weight of both obese and non-obese animals.